Potensi Nano Analog RN-18 (NARN-18) Berbasis Nanopartikel PLGA-CS-PEG dalam Penatalaksanaan HIV-1 - Gede Setula Narayana; I Kadek Wahyu Putra Dyatmika; Widia Danis Swari; I Gede Putu Supadmanaba (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2020)
Acquired Immune Deficiency Syndrome (AIDS) is the cause of death of million people in the world in 2016. The prevalence of Human Immunodeficiency Virus-1 (HIV-1) infection in Indonesia is still high and number of death caused by HIV-1-related diseases shows an apprehensive number. Treatment of HIV/AIDS nowadays is not effective to eradicate HIV-1 and also cause adverse effects. Previous research found RN-18 as a specific antagonistic molecule for viral infectivity factor (Vif) that can trigger Vif degradation and maintain intracellular A3G level. The aim of this review is to examine the potential of NARN-18 based PLGA-CS-PEG nanoparticles through oral administration in the management of HIV-1 infection. Method of this article is using literature review method. Literature searching is done by using “A3G”, “HIV-1”, “PLGA-CS-PEG”, “RN-18”, and “Vif” as keywords in search engine. 13a molecule, that is the analogue of RN-18, is used in the modality because it has better effectiveness and solubility compared with RN-18. By using PLGA, PEG, and chitosan (CS) as nanoparticles that carries RN-18 analogue makes the modality can be taken orally and targets T cell as soon as it enters the blood stream. It also can increase the efficiency of drug release and drug loading of the modality. NARN-18 constructed by using PLGA-PEG-CS nanoparticle makes the modality can be administered orally, increase its half-life in the body, and also increase the inhibition effect of RN-18 analogue. Therefore, this combination is one of the potential therapy in HIV-1 infection treatment.